The minimum wage and its relationship to the basket (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2015)
The purpose of this essay is to explain the relationship of the basic basket variables and minimum wage. Our purpose is to emphasize the gap between the two variables. The methodology of this paper is descriptive analytic where the behavior of the variables determining the minimum wage be evaluated. From the economic point of view in Nicaragua the problem is this: low wages with high prices of basic food products. With this result it is evident that further developments will occur in the gap of minimum wage and cost of the basket, making every day a utopia minimum wage equal to the cost of the basket. DOI: http://dx.doi.org/10.5377/reice.v2i4.1729 REICE Vol. 2, No. 4, julio-diciembre 2014: 110-124
Keywords: Minimum Wage; Basic Basket; Consumer Price Index; Inflation Economic Growth